Profil Kemampuan Literasi Teknologi Siswa SMP Kelas VII dalam Pelaksanaan Pembelajaran IPA - Ayu Lilis Suryana*; Dadan Rosana; Insih Wilujeng; Suyanta Suyanta; Novita Widhi Widyapuraya (Jurnal Pendidikan Sains Indonesia, 2023)
Changing times in the 4.0 era requires humans to utilize technology in all activities to make it more accessible. One way that can be done in the world of education is to increase students' technological literacy. The purpose of this study was to determine students' technological literacy abilities in science learning class VII A and VII B of SMPN 1 Depok, especially on global warming material. This research uses a qualitative descriptive research type. The population in this study were students in class VII A and VIII B of SMPN 01 Depok Yogyakarta for the 2022-2023 academic year consisting of 30 and 28 students using a purposive sampling technique. Data collection techniques consist of interviews, observation and questionnaires. The instruments consist of interview sheets, observations and technological literacy questionnaires that have been validated by expert lecturers. The results obtained from the questionnaire get 3.00 in the high category. However, the results of observational research show that the level of students' technological literacy in science learning still needs to be improved, especially on indicators of knowing the advantages of various technologies and indicators of using multimedia features in learning. The level of ability that is less than optimal in several indicators is due to technological literacy that has not been integrated with the learning and assignment of science subjects. This research is important because it can be used as input for teachers to carry out learning by supporting students' technological literacy